Detection of Cistanches Herba (Rou Cong Rong) Medicinal Products Using Species-Specific Nucleotide Signatures - Wang, Xiao-yue; Xu, Rong; Chen, Jun; Song, Jing-yuan; Newmaster, Steven-G; Han, Jian-ping; Zhang, Zheng; Chen, Shi-lin (Frontiers in Plant Science, 2018)
Cistanches Herba is a medicinal plant with tonification properties commonly used in Asia. Due to the imbalance of demand and supply, adulterants are frequently added for profit. However, there is no regulatory oversight because quality control tools are not sufficient to identify heavily processed products. Thus, a novel molecular tool based on nucleotide signatures and species-specific primers was developed. The ITS2 regions from 251 Cistanches Herba and adulterant samples were sequenced. Based on SNP sites, four nucleotide signatures within 30~37 bp and six species-specific primers were developed. In addition, they were validated by artificial experimental mixtures of six different species and different ratios. This method was also applied to detect 66 Cistanches Herba products on the market, including extracts and Chinese patent medicines. The results demonstrated the utility of nucleotide signatures in identifying adulterants in mixtures. Market study exposed 36.4% adulteration, of which 19.7% were adulterated with Cynomorium songaricum or Cistanche sinensis, and 16.7% were substituted with Cy. songaricum, Ci. sinensis or Boschniakia rossica. The results also revealed Cy. songaricum as the most common adulterant in the market. Thus, we recommend the use of species-specific nucleotide signatures for regulating adulteration and verifying medicinal product supply chain quality assurance, especially for processed products with degraded DNA.